Cognitive behavioural treatment of chronic fatigue syndrome: an in-depth case study - Rusch, Mary L (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
Chronic Fatigue Syndrome (CFS) is a chronic disabling condition characterised by persistent physical and mental fatigue, and a variety of somatic, psychological and neurological symptoms. The aetiology of CFS is unknown and the cause of the illness remains controversial. Cognitive-behavioural therapy (CBT) is a non-pharmacological treatment approach that has been shown to be effective in treating patients with CFS. It is based on a model that hypothesises that certain maladaptive thoughts and dysfunctional beliefs may contribute to self-defeating behaviour that perpetuates symptoms and disability, and thereby impedes recovery. The main aim of this study was to critically examine the cognitive-behavioural approach of CFS outlined by Sharpe, Chalder, Palmer & Wessely (1997) by conducting three in-depth case studies. An additional aim was to present a full cognitive developmental case conceptualisation of CFS based on the theories of Leahy (1996) and Young (1994). This case study evaluated the effectiveness of a CBT treatment programme in a 48-year-old Caucasian woman diagnosed with CFS for three years. The treatment consisted of sixteen sessions of CBT and was evaluated both quantitatively and qualitatively. On the basis of this study, a set of core maladaptive schema in the area of disconnection and rejection was identified. In addition, it was found that specific compensatory schemas had developed to offset the core maladaptive schemas and that this compensatory strategy played an important role in maintaining the condition. The results also showed a significant decline in fatigue coupled with a moderate decline in functional disability and depression. A one-month follow-up interview revealed evidence of a substantial consolidation of therapeutic gains in that the improvements observed at the end of the treatment were sustained. Finally, the feasibility of incorporating a cognitive-developmental and/or schema-focused model into the standard CBT treatment model is discussed and the case study method as a research toll is evaluated in light of the findings.
Keywords: Chronic fatigue syndrome; Chronic fatigue syndrome -- Psychological aspects; Chronic fatigue syndrome -- Exercise therapy; Chronic fatigue syndrome -- Treatment